In Situ Synthesis of Silver Nanoparticles for Ag‐NP/Cotton Nanocomposite and Its Bactericidal Effect. Issue 11 (29th August 2017) - Parham, Shokoh; Nemati, Mahdieh; Sadir, Sahba; Bagherbaigi, Saeedeh; Wicaksono, Dedy H.B.; Nur, Hadi
Abstract : For years, nanotechnology has been considered as an important field that has opened new opportunities for extensive research. In biomedical applications, of all the metal nanoparticles, silver nanoparticles (Ag‐NPs) have played an important role because of their antibacterial properties. Ag‐NPs have been demonstrated to possess antibacterial properties in many applications. However, the minimum number of NPs required on the surface to prevent bacterial growth is yet to be determined. It is worthwhile studying the decrease of bacterial growth rate or the level of inhibition as a function of the size or density of NPs. Therefore, in this paper we discuss the size of the NPs that can stimulate the bactericidal property. It should also be noted that NPs larger than 100 nm might not be effective against bacteria. Moreover, this study employs polyvinyl pyrrolidone (PVP) and cellulose as reductants to form strong covalent bonds under UV light, which can help synthesize Ag‐NP/cotton nanocomposites. This type of nanocomposite displays high cell viability and improved antimicrobial activity. A fairly simple application involves the use of UV light to increase particle distribution and impart bactericidal property. Abstract : A nanocomposite of silver nanoparticles and cotton prepared by in situ synthesis displays high cell viability and improved antimicrobial activity. The features of the composite show the potential of this easy and environmentally friendly preparation method in biomedical applications.